(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Calculation of performance of sectors within the economy is vitallyimportant for analyzing and allocation of funds to different purposes.Empirical evidence and the use of secondary data reveal that different sectorsworking in the economy could be prioritized according to the contribution madeby them to Gross State Domestic Product (GSDP). Due to the low leveldevelopment and scarcity of credit, some sectors in the economy are standstilland have less contribution to Gross State Domestic Product. The increasingtrend of Gross Domestic Product is the very common feature of development, butunequal contribution of different sectors to GSDP signifying the occurrence ofvarying degrees of development, and this is the more concern of this paper.This paper mainly tries to examine the relative contributions and importance ofdifferent working sectors to the Gross State Domestic Product.